2020
DOI: 10.3390/medicina56070363
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Novel Anticoagulants on the Upper Gastrointestinal Tract Mucosa

Abstract: Background and objectives: Although treatment with novel oral non-vitamin K antagonist 3anticoagulants (NOACs) is associated with an overall decrease in hemorrhagic complications compared to warfarin, the incidence of gastrointestinal bleeding remains contradictory. Materials and Methods: After the exclusion of patients with pre-existing pathological lesions in the upper gastrointestinal tract (GIT) on esophageal-gastroduodenoscopy (EGD) at entry, a cohort of 80 patients (mean age of 74.8 ± 2.0 years) was rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
9
1
3
Order By: Relevance
“…However, according to the results of the Ko YJ study, based on the Korea Institute of Drug Safety and Risk Management–Korea database, it was found that rivaroxaban was associated with the more frequent development of bleeding events than treatment with dabigatran or apixaban [ 21 ]. The results of our study and data from a number of other studies did not identify any significant differences between the different NOACs in the incidence of bleeding [ 22 , 23 ].…”
Section: Discussioncontrasting
confidence: 51%
“…However, according to the results of the Ko YJ study, based on the Korea Institute of Drug Safety and Risk Management–Korea database, it was found that rivaroxaban was associated with the more frequent development of bleeding events than treatment with dabigatran or apixaban [ 21 ]. The results of our study and data from a number of other studies did not identify any significant differences between the different NOACs in the incidence of bleeding [ 22 , 23 ].…”
Section: Discussioncontrasting
confidence: 51%
“…Особый интерес представляет публикация результатов наблюдения влияния 3-х ПОАК на слизистую желудочно-кишечного тракта, которое показало, что через 3 мес. терапии нет достоверных различий в частоте клинически и эндоскопически значимых кровотечений из желудочно-кишечного тракта ни на одном из ПОАК в сравнении с варфарином, а основной причиной кровотечений авторы называют присутствие Helicobacter pylori [34]. Эти данные указывают на первостепенное значение обследования пациентов до начала длительной антикоагулянтной терапии.…”
Section: инсульт в анамнезеunclassified
“…Соответственно, чем более коморбиден пациент, тем выше риск кровотечений независимо от принимаемого антикоагулянта, а значит важно искать причину и модифицировать ее, вместо поиска "самого безопасного" антикоагулянта [40,41].…”
Section: выбор поак с учетом имеющейся доказательной базыunclassified